The Influence of Work Environment and Work Motivation on Teacher Work Discipline (Survey on Teachers of SMK Muhammadiyah Tasikmalaya) - Teten Syahrul Ramdhona; Kusuma Agdhi Rahwana; Arga Sutrisna (Penerbit Jurnal Indonesia, 2022)
This research was conducted with the aim of knowing the effect of the work environment and work motivation on teacher work discipline. A case study of teachers at Vocational High School Muhammadiyah Tasikmalaya. The method used in this study is a survey method using data obtained directly through questionnaires distributed to 30 respondents who are teachers of Vocational High School Muhammdiyah Tasikmalaya. The technique used in this research is Path Analysis. The results showed that: (1) the work environment had a positive and significant effect on the work Motivation of teachers at Vocational High School Muhammadiyah Tasikmalaya; (2) the work environment has a positive and significant effect on work discipline; (3) there is a positive and significant influence of work motivation on work discipline for teacher of Vocational High School Muhammadiyah Tasikmalaya (4) the work environment has a significant effect on work discipline through work motivation.